Untraceable Mobile Node Authentication in WSN - Kyusuk Han; Kwangjo Kim; Taeshik Shon (Sensors, 2010)
Mobility of sensor node in Wireless Sensor Networks (WSN) brings security issues such as re-authentication and tracing the node movement. However, current security researches on WSN are insufficient to support such environments since their designs only considered the static environments. In this paper, we propose the efficient node authentication and key exchange protocol that reduces the overhead in node re-authentication and also provides untraceability of mobile nodes. Compared with previous protocols, our protocol has only a third of communication and computational overhead. We expect our protocol to be the efficient solution that increases the lifetime of sensor network.